Tertiary English students’ learning motivation and critical thinking skills - Fuad Nashori; Adam Anshori; Rahmat Aziz; Infanti Wisnu Wardani (INSPIRA, 2023)
This paper highlights the importance of learning motivation and critical thinking skills to an EFL learner. Apart from gaining language ability in speaking, reading, listening, and writing, an EFL learner must also be equipped with other factors or skills to succeed. Hence, this study aimed to determine how much learning motivation correlates with critical thinking skills amongst tertiary English Language Education Department students at Universitas Islam Indonesia. By deploying a purposive sampling technique, 50 participants were involved in this study. It comprises 16 male students (32%) and 34 female students (68%). Critical thinking and learning motivation questionnaires were utilized to garner the data, and the data were further analyzed using the product-moment correlation. This study also utilizes in-depth interviews to gain more perspective on critical thinking, learning motivation, and how it shapes behavior. The results demonstrated that learning motivation positively and significantly correlated with critical thinking skills. Across varied levels, contexts, and periods, the current study confirmed the persistent theory concerning the correlation between learning motivation and critical thinking, as prior related studies already demonstrated. Further studies are called to be conducted by engaging a more significant number of samples to reveal broader insights